The green market transition : carbon taxes, energy subsidies and smart instrument mixes - Weishaar, S. E., 1976-; Kreiser, Lawrence A.; Milne, Janet E., 1951-; Ashiabor, Hope; Mehling, Michael (Critical issues in environmental taxation, 2017)
The Paris Agreement on climate change constitutes an important milestone in international climate negotiations. Its key objective is the strengthening of the global response to climate change by transitioning the world to an increasingly green economy. In this book, environmental tax and climate law experts address the various issues surrounding green market transitions. Key chapters examine carbon taxes and systems of implementation, energy subsidies, and support schemes for carbon and energy policies. Using a multitude of international case studies, several contributing authors reflect on the underlying policy dynamics and the constraints of various fiscal measures. In addition, this timely work considers the important issue of smart instrument mixes, going beyond instrument choice to examine how they can work in harmony together. Astute and engaging, this book is a vital companion for students and scholars in environmental law, economics and sustainability. Its practical approach also renders it an excellent guide for policy makers and those involved in fiscal reform and green market transition.